The Circus and Aerial Performances: : simulation of risk and concealment of pain - Leles, Marilia Teodoro de; Camargo, Robson Corrêa de (Revista Brasileira de Estudos da Presença, 2022)
The article examines the relationship between risk and pain as elements present in the construction, exhibition and reception of aerial circus shows. There is a bibliographic review on the theme of pain and risk, analyzing them as perceptive processes that encompass biological, affective and cultural issues. Finally, it describes the aerial circus performance, identifying that the relationship between these phenomena appears as an imbricated paradox in its presentation.